간전이 바터팽대부암의 항암화학요법에 병용한 한의치료 1례 - 오승윤; 박수정; Seung-Yun Oh; Soo-Jung Park (大韓癌韓醫學會誌, 2023)
Objectives: To report the reduction of adverse effects of chemotherapy and improvement in the quality of life in recurrent liver metastasis by Korean medicine treatments. Methods: In 2018, a 75-year-old male patient underwent surgery for primary cancer in the ampulla of Vater. In 2021, he was diagnosed with recurrent liver metastasis. Following the failure of tumor treatment with gemcitabine/cisplatin and the development of severe side effects, he decided to discontinue chemotherapy. Subsequently, with a significantly enlarged liver tumor, he resumed capecitabine/oxaliplatin treatment, alongside moxibustion, acupuncture, and herbal prescriptions from August 2021 to August 2023. The changes of chief complaints, abdominal CT, and laboratory findings were investigated. Results: After combined treatment of Korean traditional medicine and chemotherapy, the mass was decreased. Laboratory findings, and chief complaints of hand-foot syndrome, fatigue, abdominal distension, nausea and anorexia were improved. Conclustions: This case study suggests that Korean traditional medicine is effective in enhancing anticancer effects, suppressing the side effects of chemotherapy, and improving general conditions.